Development of Functional Literacy Through Creative Thinking Tasks (Journal of Pedagogical Inventions and Practices, 2023)
The article develops proposals and recommendations for preparing students for an international assessment program using creative thinking tasks from international initial studies, as well as for the development of reading literacy, mathematical literacy, global competence and natural science literacy, as well as for the adaptation of students to the integration of sciences in life